Analysis of the models in forecastig kinematic scheme education nitrogen oxides in the solid fuel - Korzilova I. E.; Vizgavlyust N. V. Nataliya Viktorovna; Buvakov K. V. Konstantin Vladimirovich; Taylasheva T. S. Tatiana Sergeevna; Starchenko A. V. Aleksandr Vasiljevich (Applied engineering, 2016)
Title screen